Eliciting Reliable Information in Investigative Interviews - Vrij, Aldert; Hope, Lorraine; Fisher, Ronald P. (Policy insights from the behavioral and brain sciences, 2014)
Interviews are an important part of investigations, as the information obtained from interviewees generates leads and evidence. However, for several psychological reasons, even cooperative victims and witnesses do not spontaneously report all the information they know, and their accounts may incorporate errors. Furthermore, suspects often deliberately withhold information or may attempt to mislead the interviewer. First, known psychological factors promote complete and accurate reports by cooperative witnesses and victims. Such factors relate to the social dynamics between the witness and interviewer (e.g., developing rapport), the interviewee’s and the interviewer’s cognitive processes, and communication between the witness and interviewer. Empirical research examines interviewing techniques that incorporate these interviewing principles. Second, some suspects may be reluctant to volunteer information. Typically, two interview styles encourage suspects to talk: An information-gathering style seeks to establish rapport with interviewees and uses open-ended exploratory questions to elicit information and establish guilt. An accusatorial style uses closed-ended confirmatory questions to elicit confessions. The former approach performs better at eliciting accurate information and true confessions. In any interview, the ability to detect truth from deceit is important. Many lie detection techniques are based on listening to speech or observing behavior, but only some discriminate between truth and deceit.